2015
DOI: 10.1002/2014jd022121
|View full text |Cite
|
Sign up to set email alerts
|

Upper tropospheric ozone production from lightning NOx‐impacted convection: Smoke ingestion case study from the DC3 campaign

Abstract: As part of the Deep Convective Cloud and Chemistry (DC3) experiment, the National Science Foundation/National Center for Atmospheric Research (NCAR) Gulfstream-V (GV) and NASA DC-8 research aircraft probed the chemical composition of the inflow and outflow of two convective storms (north storm, NS, south storm, SS) originating in the Colorado region on 22 June 2012, a time when the High Park wildfire was active in the area. A wide range of trace species were measured on board both aircraft including biomass bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
119
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(125 citation statements)
references
References 97 publications
(156 reference statements)
0
119
0
Order By: Relevance
“…The median daily net ozone production for the HOOVER case is 22.67 ppbv d −1 (range: 19.47-26.11 ppbv d −1 ) and about a factor of 2-4 larger than values reported in the literature for NH mid-latitudes, e.g. ∼ 15 ppbv d −1 during PRESTORM, Oklahoma (Pickering et al, 1990(Pickering et al, , 1992a, 10-13 ppbv d −1 during STERAO-A over North America (DeCaria et al, 2005), up to 5 ppbv during EULINOX over Europe (Ott et al, 2007), and 5-7 ppbv d −1 during DC3 over North America (Apel et al, 2015).…”
Section: The Influence Of Deep Convection On Noprmentioning
confidence: 52%
“…The median daily net ozone production for the HOOVER case is 22.67 ppbv d −1 (range: 19.47-26.11 ppbv d −1 ) and about a factor of 2-4 larger than values reported in the literature for NH mid-latitudes, e.g. ∼ 15 ppbv d −1 during PRESTORM, Oklahoma (Pickering et al, 1990(Pickering et al, , 1992a, 10-13 ppbv d −1 during STERAO-A over North America (DeCaria et al, 2005), up to 5 ppbv during EULINOX over Europe (Ott et al, 2007), and 5-7 ppbv d −1 during DC3 over North America (Apel et al, 2015).…”
Section: The Influence Of Deep Convection On Noprmentioning
confidence: 52%
“…This is a particularly important region because it is the region of most efficient ozone production (Dahlmann et al, 2011). Understanding how the magnitude of lightning flash rate or concentration of emissions affects ozone production is an ongoing area of research, and so far has focussed on individual storms or small regions (Allen and Pickering, 2002;DeCaria et al, 2005;Apel et al, 2015). DeCaria et al (2005) found that whilst there was little ozone enhancement at the time of the storm, there was much more ozone production downstream in the following days.…”
Section: Introductionmentioning
confidence: 99%
“…The auxiliary gas-phase data used in this analysis are carbon monoxide (CO) by vacuum UV resonance fluorescence (Gerbig et al, 1999); nitric oxide (NO) and nitrogen dioxide (NO 2 ) by chemiluminescence (Ridley et al, 2004); ethane (C 2 H 6 ) by infrared spectrometry (Richter et al, 2015); aromatic and biogenic species by online proton-transfer-reaction mass spectrometry (Lindinger et al, 1998;de Gouw and Warneke, 2007); hydrogen cyanide (HCN); i-pentane and npentane by online cryogenic gas chromatography-mass spectrometry (GC-MS) (Apel et al, 2015); methylcyclohexane and n-octane by offline analysis of whole air canister samples (WAS) by GC-MS (Colman et al, 2001); nitric acid (HNO 3 ) by chemical ionization mass spectrometry (CIMS) using SF − 6 as the reagent ion (Huey et al, 1998); peroxyacyl nitrates (PAN and PPN) by I − CIMS (Zheng et al, 2011); alkyl nitrates by thermal dissociation laser-induced fluorescence (Day et al, 2002); and hydroxyl (OH), hydroperoxy (HO 2 ), and alkyl peroxy (RO 2 ) radicals by CIMS (Mauldin et al, 1998;Hornbrook et al, 2011;Ren et al, 2012). NO y was calculated by summing up the individually measured nitrogen oxide species, namely NO, NO 2 , HNO 3 , particulate nitrate, PAN, PPN, and alkyl nitrates.…”
Section: Measurementsmentioning
confidence: 99%